Le traité de réciprocité 1854-1866 - Latulippe, Jean-Guy (L'Actualité économique, 1976)
Abstract"Reciprocity is a relation between two independent powers, such that the citizens of each are guaranteed certain commercial privileges at the hands of the others". The arrangement obtained under the Reciprocity Treaty of 1854 might perhaps be appropriately described as a partial "free-trade area" rather than as a "customs union" since the United States and the British North American Provinces were not assumed to draw up a common tariff schedule for their imports from the outside countries. Each participant maintains its own duties against other countries or even colonies.The Reciprocity Treaty permitted free access in the coastal fisheries to Americans and abolished duties on a wide range of natural products (grain, flour, fish, livestock, coal, timber and other less important natural produce). At the same time, American vessels were admitted to the use of Canadian canals on the same terms as British and colonial vessels. Reciprocity was to apply to Canadian vessels going to United States.In the late 1840's the B.N.A. Provinces were faced by that policy which the literature has called "Little Englandism". When Britain repealed the corn laws and gradually the preferential tariffs on timber the B.N.A. Provinces were shocked to be left on their own. A new commercial system had to be developed: reciprocity was the answer. But, it could have been something else: protection or annexion.The direction of the external trade changes with the Reciprocity Treaty. Before 1851, Britain was Canada's main partner (59% of Canada's Exports). But a decade later, the United States was both Canada's major supplier and its best customer. Neither the Treaty nor the loss of preference in the British Market succeeded in destroying the Trade of B.N.A. Provinces with the United Kingdom. In fact, trade with Britain was greater in 1865 than in 1854. Later, in 1870, Britain took back its leading position. What we see is a diversion of trade from Britain to the United States and back to Britain where the basic commercial connections were well established.The Treaty was disappointing for the "dream" of using the St. Lawrence as the main route to capture the trade of the West did not materialize.The consequence of abrogation was less unfortunate than had in some quarters been anticipated. The Treaty came late after the abolition of the preferential tariffs, and it was disturbed by major events (the crisis of 1857; the American Civil War). After the treaty, recovery of the American currency reconstruction, proximity of the two countries, a new boom in foreign investment in Canada, etc., combined to reduce considerably the potential blow to Canada of the Abrogation. The agreement lasted for twelve years and was finally overwhelmed by the rising tide of protectionism and commercial jealousies and political hostilities of the time.Reciprocity, Confederation, the Nation Policy, the St. Lawrence Seaway (1840/1950), the National Corporations, the pipelines are all the elements of the same continuum: economic and political integration of isolated markets in North America.